Understanding patients’ spiritual issues during hospitalisation: a qualitative study - Wan Mamat, Wan Hasliza; Hairulisa@Mohd Hairi, Nur Alia; Mohamad Shariff, Nurasikin; Che Ahmad, Aminudin; Salah, Machouche; Jaafar, Siti Nur Illiani (Transnational Press London Ltd, 2024)
Introduction: A holistic approach to patient care emphasises the need to consider not only physical and mental health but also spiritual well- being. Objective: This study aimed to explore patients’ spiritual issues during hospitalisation. Methods: This study employed a qualitative design. Ten participants were recruited through purposive sampling. They participated in in-depth, face-to-face, audio-recorded, one-time interviews using a semi-structured interview guide. All interviews analysed using thematic analysis. Results: Five themes were identified concerning patients’ spiritual issues during hospitalisation: 1) physical and emotional suffering, 2) unexpected health diagnoses, 3) loneliness of illness, 4) emotional impact of hospitalisation, and 5) neglected religious practice. Conclusion: Patients require more than just medical interventions; they also need spiritual care to aid their healing process and treatment. These findings highlight the importance of healthcare professionals conducting spiritual assessments of patients and taking necessary actions when they are admitted to hospital.